2019
DOI: 10.35219/foodtechnology.2019.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Overview of sodium nitrite as a multifunctional meat-curing ingredient

Abstract: Sodium nitrite is a meat-curing ingredient responsible for developing and fixing the sensory product attributes, also having a strong antimicrobial activity. However, it is associated with nitrosamine formation. Therefore, there is consumer demand for low-nitrite or nitrite-free meat products. In order to develop these products it is essential to understand the complex functions of sodium nitrite in meat-curing. This review summarizes the positive effects of nitrite in meatcuring, and points out that sodium ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In contrast to the DPPH method, ABTS ·+ is soluble not only in organic but also in aqueous media, and therefore lipophilic and hydrophilic nature of various compounds can be measured [ 48 , 49 ]. The FRAP method is connected to the reduction of iron ion from form Fe 3+ (ferric state) to Fe 2+ (ferrous state) which is not only connected with the color of meat products but also with its durability [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the DPPH method, ABTS ·+ is soluble not only in organic but also in aqueous media, and therefore lipophilic and hydrophilic nature of various compounds can be measured [ 48 , 49 ]. The FRAP method is connected to the reduction of iron ion from form Fe 3+ (ferric state) to Fe 2+ (ferrous state) which is not only connected with the color of meat products but also with its durability [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…67,68 Nitrite is often added into fermented meat products and fermented fish to prevent the emergence of Clostridium botulinum and its toxins 69 while promoting the formation of color and flavor. 70 The nitrite peak could be detected in the early stage of low-sodium fermented vegetables, which was correlated with the metabolism of enterobacteria, such as Escherichia coli and Serratia marcescens. 71 Consequently, the potential risk of the surge in the accumulation of nitrosamines exists in low-sodium fermented vegetable products, fermented meat products, and fermented fish.…”
Section: Nitrosaminesmentioning
confidence: 93%
“…Nitrosamines could be formed by the reaction of nitrite with secondary amines, especially in acidic conditions. Nitrite and BAs are found in most fermented foods, and their concentration varies dramatically. , Nitrite is often added into fermented meat products and fermented fish to prevent the emergence of Clostridium botulinum and its toxins while promoting the formation of color and flavor . The nitrite peak could be detected in the early stage of low-sodium fermented vegetables, which was correlated with the metabolism of enterobacteria, such as Escherichia coli and Serratia marcescens .…”
Section: Challenges Of Sodium Reduction In Traditional Fermented Foodsmentioning
confidence: 99%
“…Stoica (2019) indicated that nitrite should be added at an amount of 25–50 mg kg −1 to create an acceptable cured colour in meat, whereas other authors (Rivera et al ., 2019) stated that an amount of 10–15 mg kg −1 is sufficient for achieving similar pigment fixation. It seems that the desired colour and its maintenance can be achieved with 50 mg kg −1 of sodium nitrite together with fortification of herb extract.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the strong antioxidant properties of nitrite itself are linked with the stabilisation of myoglobin haem iron, because myoglobin is also responsible for initiating protein and lipid oxidation (nitrosylmyoglobin presents antioxidant properties). In other words, substances with antioxidant activity exhibit electron‐donating properties, in this case (Alahakoon et al ., 2015; Stoica, 2019). Due to the high concentrations of phenolic substances in aqueous extract, it could be supposed that WH extract added to canned meat contributed to stabilising the iron ions (Table 1).…”
Section: Resultsmentioning
confidence: 99%